Perancangan Teknologi Sederhana Untuk Membangkitkan Microwave Plasma Dalam Cairan - Muhammad Firdan Nurdin (Elektrika Borneo, 2021)
Plasma technology has interested, especially plasma in liquid which can be applied in the process of gas productions, water treatment, and nanomaterial productions. The purpose of this study is to make a simple technology 2.45 GHz microwave plasma and generate in the variation of liquids such as distilled water, seawater, and X-Ray liquid waste by utilizing a microwave oven, as well as to observe the effect of vacuum pressure variations. A microwave oven was modified by integrating a waveguide and a plasma reactor for plasma observation. The results, plasma was generated in distilled water at a vacuum pressure of about 7 kPa, X-Ray liquid waste at a vacuum pressure of about 13 kPa, and seawater at a vacuum pressure of about 34 kPa.